Acer tegmentosum Maxim and Bacillus subtilis-fermented products inhibit TNF-α-induced endothelial inflammation and vascular dysfunction of the retina: the role of tyrosol moiety in active compounds targeting Glu230 in SIRT1 - Nguyen, Phuc Anh; Won, Jong Soon; Cho, Min Kyung (Frontiers in Pharmacology, 2024)
Acer tegmentosum Maxim (AT) is a traditional medicine plant used to treat hepatic, neurological diseases and cancer. However, the beneficial effects of AT on endothelial dysfunction have not yet been reported. In this study, we evaluated the effects of AT and the main compounds against TNF--mediated inflammatory responses and their possible mechanism of action. Anti-inflammatory effect and its molecular mechanism were analyzed by adhesion assay, immunoblotting, promoter-luciferase assay, ELISA, RT-PCR, immunocytochemistry, immunoprecipitation, siRNA gene knockdown, docking and molecular dynamic analysis. AT and its compounds, salidroside and tyrosol, reduced TNF-Bacillus subtilis converted salidroside to tyrosol, the salidroside's aglycone. The fermented AT product (ATF) potently inhibited TNF--mediated monocyte adhesion, with higher potency than AT. AT or AT F abrogated TNF--induced expression of adhesion molecules (VCAM-1, ICAM-1) and production of MCP-1 with inhibition of phosphorylated MAP kinases. TNF--mediated NF-B transactivation and RelA/p65 acetylation were suppressed by AT and ATF through the interaction of NF-B with Sirtuin-1 (SIRT1), an NAD +dependent histone deacetylase. Sirt1 gene knockdown diminished the protective effects of AT and ATF against TNF--mediated signalling and inflammatory response. Interestingly, SIRT1 protein expression was significantly increased by AT F and tyrosol rather than by AT and salidroside, respectively. Docking simulation showed that the tyrosol moiety is critical for the interaction with Glu 230 of SIRT1 (PDB ID: 4ZZH and 4ZZJ) for the deacetylase activity. Molecular simulation revealed that tyrosol can induce the movement of the Nterminal domain toward the catalytic domain of SIRT1. This study demonstrates the potential of AT and ATF to prevent endothelial inflammation by the MAPK/NF-κB/SIRT1 signalling pathways and targeting of the tyrosol moiety to Glu 230 in SIRT1.